Peran Pelatih dalam Pembinaan Prestasi Atlet pada Organisasi Taekwondo Profesional - Tifani Faradita Muslima; Fathul Himam (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2016)
This research was conducted with the aim of seeking a more in-depth understanding of the training strategies carried out by trainers on professional taekwondo athletes in building athletic achievements. Research uses a qualitative approach with phenomenological methods to capture phenomena that occur in a problem. The analysis is used through the epoche process, horizonalization with the process of reducing phenomenology, imaginative variation, and taking the synthesis of the meaning and essence of the phenomenon under study. The credibility of the results of the study was carried out using the triangulation method and member checking. The results of the study indicate that the strategy of coaching carried out by the trainer is to build support through communication, brotherhood and organizational support; learning through learning from experience and self-development; and coaching through mental coaching, achieving achievement, and sensitivity to athletes.